IMPACT OF STAINLESS STEEL GUIDE TUBES ON THE REACTIVITY PARAMETERS OF THE NPP KRŠKO CORE - Kromar, Marjan; Kurinčič, Bojan (Journal of Energy Technology, 2024)
PWR fuel assemblies with Zircaloy-based guide tubes experience some level of bowing during nuclear plant operation. Severe bowing could present difficulties impacting plant performance. Bowing could be mitigated with a reintroduction of stainless steel guide tubes. The impact of such tubes on the reactivity parameters of NPP Krško fuel is investigated in this paper. Ananalysis has shown that the stainless steel guide tubes lower critical boron concentration by about 140 ppm. To compensate this effect and retain the cycle length, fuel enrichment should be increased by 0.2%. The combined changes result in a 100 ppm higher boron concentration at the beginning of the fuel cycle and increase isothermal temperature coefficient by approximately 1 pcm/K compared to the Zircaloy-based fuel. Core power distributions and power peaking factors remain almost the same. Increased thermal neutron shielding in the stainless steel guide tubes lowers control rods worth up to 3% in relative terms. Analysis has shown that the replacement of the Zircaloy with stainless steel as a guide tube material could become a viable solution to mitigate fuel bowing problems.